Amygdala Enlargement in Patients with Mesial Temporal Lobe Epilepsy without Hippocampal Sclerosis - Coan, Ana C.; Morita, Marcia Elisabete; Campos, Brunno M.; Yasuda, Clarissa L.; Cendes, Fernando (Frontiers in Neurology, 2013)
Purpose: Patients with mesial temporal lobe epilepsy (MTLE) without MRI abnormalities (MTLE-NL) represent a challenge for definition of underlying pathology and for presurgical evaluation. In a recent study we observed significant amygdala enlargement in 14% of MTLE patients with MRI signs of HS. Areas of gray matter volume (GMV) increase could represent structural abnormalities related to the epileptogenic zone or part of a developmental abnormality. Our objective was to look for undetected areas of increased GMV in MTLE-NL using post processing MRI techniques to better understand the pathophysiology of this condition. Methods: We evaluated 66 patients with MTLE-NL on visual analysis and 82 controls. Voxel-based morphometry (VBM) group analysis was performed with VBM8/SPM8 looking for areas of increased GMV. We then performed automatic amygdala volumetry using Freesurfer software and T2 relaxometry to confirm VBM findings. Results: VBM group-analysis demonstrated increased amygdala volume in the MTLE-NL group compared to controls. Individual volumetric analysis confirmed amygdala enlargement (AE) in eight (12%) patients. Overall, from all patients with AE and defined epileptic focus, four (57%) had the predominant increased volume ipsilateral to the epileptic focus. These results were cross-validated by a secondary VBM analysis including subgroups of patients according to the volumetric data. T2 relaxometry demonstrated no amygdala hyperintense signal in any individual with significant amygdala enlargement. There were no clinical differences between patients with and without AE. Discussion: This exploratory study demonstrates the occurrence of AE in 12% of patients with MTLE-NL. This finding supports the hypothesis that there might be a subgroup of patients with MTLE-NL in which the enlarged amygdala could be related to the epileptogenic process. Further studies are necessary but this finding could be of great importance in the understanding of MTLE-NL.